2014
DOI: 10.1002/pssr.201409284
|View full text |Cite
|
Sign up to set email alerts
|

Non-magnetic defects in the bulk of two-dimensional topological insulators

Abstract: We found that non‐magnetic defects in two‐dimensional topological insulators induce bound states of two kinds for each spin orientation: electron‐ and hole‐like states. Depending on the sign of the defect potential these states can be also of two kinds with different distribution of the electron density. The density has a maximum or minimum in the center. A surprising effect caused by the topological order is a singular dependence of the bound‐state energy on the defect potential. (© 2014 WILEY‐VCH Verlag G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
2
19
0
2
Order By: Relevance
“…The contradictions are clearly seen in the spatial distributions of the total density ρ and the pseudospin components of the densities, as well as in the dependence of the densities on the impurity potential. The results we have obtained here very well agree with the direct calculations within the continuous model of the isolated defect 24 . The bound state energies depend also on the parameter a, defined through the parameters of the BHZ model by Eq.…”
Section: Bound States In the Bulksupporting
confidence: 86%
See 3 more Smart Citations
“…The contradictions are clearly seen in the spatial distributions of the total density ρ and the pseudospin components of the densities, as well as in the dependence of the densities on the impurity potential. The results we have obtained here very well agree with the direct calculations within the continuous model of the isolated defect 24 . The bound state energies depend also on the parameter a, defined through the parameters of the BHZ model by Eq.…”
Section: Bound States In the Bulksupporting
confidence: 86%
“…This simplification allows us to calculate analytically the integrals over p in Eqs. (11) and (24). The subsequent integration over k is done numerically.…”
Section: Defect-induced States Near the Boundarymentioning
confidence: 99%
See 2 more Smart Citations
“…In the edge states the electrons move along the boundary and their spin is locked to the momentum because of strong spin-orbit interaction. In recent works [15,16] we have studied the electronic states induced by nonmagnetic defects and found that a defect with a short-range potential creates two bound states in contrast to topologically trivial insulators where only one bound state exists at such a defect. These states differ in both the pseudospin structure and the spatial distribution of the particle density.…”
Section: Introductionmentioning
confidence: 99%